2016
DOI: 10.1080/15226514.2016.1244164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different treatments of fly ash and mining soil on growth and antioxidant protection of Indian wild rice

Abstract: The aim of the present study was investigation of the effects of fly ash and mining soil on growth and antioxidant protection of two cultivars of Indian wild rice (Oryza nivara and Oryza rufipogon) for possible phytoremediation and restoration of metal-contaminated site. In this study, Indian wild rice showed significant changes in germination, growth, and biochemical parameters after exposure to different ratio of fly ash and mining soil with garden soil. There was significant reduction of germination, fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The levels of Zn and Cu in garden soil were in normal range and Mn level was very low ( Kabat Pendias, 2011 ). The results were consistent with the reported value in different fly ash deposits by Bisoi et al. (2017) , Gajić et al.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The levels of Zn and Cu in garden soil were in normal range and Mn level was very low ( Kabat Pendias, 2011 ). The results were consistent with the reported value in different fly ash deposits by Bisoi et al. (2017) , Gajić et al.…”
Section: Resultssupporting
confidence: 93%
“…Phytoremedial potential of plants can be measured through its elevated antioxidative potential with increased capacity to scavenge reactive oxygen species (ROS) ( Nadgórska-Socha et al., 2013 ). Therefore, the plant antioxidant defence system may be important to reveal its tolerance mechanisms to different metals present in contaminated soil ( Bisoi et al., 2017 ). However, relatively few reports have been published on the oxidative metabolism in higher plants under fly ash including Castor ( Bisoi et al., 2017 ; Nadgórska-Socha et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that low FA application in soil did not trigger oxidative stress whereas higher level of metals in FA amended soil causes disturbance in the cell membrane, cell disruption, interrupt various metabolic processes and causes inhibition in plant growth . Plant tolerance to heavy metal stress is directly associated with an upsurge in antioxidant enzymes to detoxify reactive oxygen species (Bisoi et al 2017). This elevation in enzymatic activity might be due to the plant defense against ROS species generated by metal ions present in FA.…”
Section: Level Of Antioxidant Enzyme Activity-mentioning
confidence: 99%
“…Various heavy metals namely Cu, Ni, Fe, Pb, Cr, Cd etc that may exhibit metal toxicity in plants. Fly ash utilization in soil systems has been tested so far for Brassica juncea, Helianthus annus [Pandey et al, 1994], Cassia siamea [Tripathi et al, 2005], Triticum aestivum [Kumar et al, 2010], rice [Bisoi et al, 2017]. The presence of nutrients allows the use of fly ash for agricultural purposes to fortify crops with nutrients, such as Se, Fe, and Zn.…”
Section: Introductionmentioning
confidence: 99%